APPLYING LINGUODIDACTIC APPROACHES TO FOREIGN LANGUAGE INSTRUCTION (KONFERENSIYA, 2025)
In the given article was considered main approaches to teaching to foreign languages from the position of linguodidactics and technique of teaching to foreign languages.